Exploration of the potential neurotransmitter or neuromodulator-like properties of harmine: evidence from synthesis to synaptic modulation - Xie, Zhejun; Cao, Ning; Li, Manlin; Wang, Hanxue; Guan, Huida; Cheng, Xuemei; Wang, Changhong (Frontiers in Pharmacology, 2025)
Background:The discovery of new neurotransmitters is crucial for the in-depth understanding of neural signal transmission, neurological disorders, and relevant treatment strategies. Emerging evidence has indicated that harmine is an important endogenous compound, and its level is closely related to different physiological and disease states. Inspired by this, we propose a hypothesis that harmine may be a potential neurotransmitter or neuromodulator and display neurotransmitter or neuromodulator-like properties. This study aims to explore the potential properties of harmine as a neurotransmitter or neuromodulator according to the essential criteria for neurotransmitters and neuromodulators.Methods:Candidate proteins for the biosynthesis of harmine were searched by local BLAST. The target protein was then recombinantly expressed, purified, and functionally validated. Subsequently, the release, metabolism, and uptake pathways of harmine were investigated using rat brain synaptosomes and primary neural cells through mass spectrometry analysis. A human proteome microarray was employed to screen for harmine-binding receptors, followed by experimental validation.Results:Adipocyte plasma membrane-associated protein isoform X1 (APMAP-X1) could effectively catalyze the Pictet-Spengler reaction in mammals to generate tetrahydroharmine, which was subsequently oxidized by myeloperoxidase (MPO) to produce harmine. Moreover, harmine could be metabolized, taken up, and released within the synaptic cleft, fulfilling the conditions for clearance and release within the synaptic cleft. Harmine also regulated the expression of neurotransmitter transporters, implying its potential neuromodulatory properties. G protein-coupled receptor 85 (GPR85) and chloride intracellular channel 2 (CLIC2) were receptors targeted by harmine in the central nervous system. Functional verification results confirmed that harmine exerted an inhibitory effect on the GPR85 and could induce cellular depolarization.Conclusion:Current findings provide preliminary evidence that harmine may exhibit neurotransmitter-like properties in certain respects and support its role as an endogenous neuromodulator. However, direct evidence supporting harmine as a neurotransmitter remains limited. Further studies are needed to clarify the precise mechanisms of harmine in neurotransmission. Our study provides a new perspective for researchers on exploring novel endogenous molecules and their significance in neurophysiology.